Forgiving, fast and slow: validity of the implicit association test for predicting differential response latencies in a transgression-recall paradigm - Fatfouta, Ramzi; Schröder-Abé, Michela; Merkl, Angela (Frontiers in Psychology, 2014)
This study examined the role of automaticity in forgiving a real-life offense. As an alternative to self-report, an Implicit Association Test (IAT) of forgiveness was developed. Implicit (IAT-measured) and explicit (self-reported) forgiveness predicted shorter response times of state forgiveness ratings. The forgiveness IAT was highly reliable, moderately stable over time, and demonstrated incremental validity. Results suggest that the newly introduced forgiveness IAT could advance personality research beyond what is known from self-report measures, further corroborating the notion of implicit forgiveness. Implications for personality assessment are discussed.